The Immunogenicity of Fractional Intradermal Doses of the Inactivated Poliovirus Vaccine Is Associated With the Size of the Intradermal Fluid Bleb. (21st April 2017) - Bibby, Jack; Saidu, Yauba; Umesi, Ama; Moneke-Anyanwoke, Ngozi; Bashorun, Adedapo O; Hydara, Mariama Badjie; Adigweme, Ikechukwu; Adetifa, Jane U; Okoye, Michael; Roberts, Elishia; Clemens, Ralf; Bandyopadhyay, Ananda S; et al.
Abstract: The immunogenicity of fractional (one-fifth, 0.1 mL) intradermal doses of the inactivated poliovirus vaccine (ID fIPV) is positively correlated with the size of the intradermal fluid bleb. Training of vaccinators for campaign and routine ID fIPV administration should focus on generating an 8- to 10-mm bleb with each injection. Clinical Trials Registration: NCT01847872